The relationship between leadership and productivity: a case study on public managers in Guilan Province, Iran - Mohammad Reza Azadehdel (Penerbit UKM, 2010)
The purpose of this study is to explore the relationship between public managers’ leadership style, their creativity, and productivity of state organizations in Guilan Province of Iran. It emphasizes the transformational and transactional leadership style exhibited by public managers during the implementation of the Reform Program. The leadership style, the ability to influence people to achieve desired goals and creativity, the ability to mingle ideas in making unusual relationship between different ideas are treated as the independent variables while the demographic characteristics of the public managers such as sex, age, education level, and experience are treated as the modifying variables. Productivity, the degree by which to measure an organization’s success at efficiently using resources to achieve objectives, is the dependent variable of the study. The study combines both the quantitative and the qualitative methods. In the quantitative section, four clusters of hypothesis are used to investigate the relationship between leadership, creativity and productivity in target population group. Findings of the study show that the dominant exhibited leadership style of public managers is the transactional style, because of the belief in the stability of the system. In the hypothesis testing most of the major hypotheses are accepted. This indicates that there is a significant correlation between public managers’ leadership style, their creativity and productivity of state organizations. Nevertheless, transactional leadership style as a single approach is not an effective style to achieve the Reform Program’s objectives, because transactional leaders did not put attention on developing followers to achieve their full potential. Hence, public managers must select the mix style of transformational and transactional leadership in order to be more effective. Results from the qualitative analysis demonstrates that the general performance of the main Reform Program’s objectives such as the performance of the Development and Planning Council, the improvement of public participation, and attraction and retention of experts and professionals, have received less favorable responses in the Reform Program. The lack of productivity and responsibility, shortcomings of the economic policies and disposition of public interest, and lack of flexible payments were due to such a reaction. However, managers believe that human resource development and structural reorganization, during the Reform Program have been generally efficient.